Understanding the Driver of Energetic Electron Precipitation Using Coordinated Multisatellite Measurements. Issue 14 (19th July 2018) - Capannolo, L.; Li, W.; Ma, Q.; Zhang, X.‐J.; Redmon, R. J.; Rodriguez, J. V.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; Engebretson, M. J.; Spence, H. E.; Reeves, G. D.
Abstract: Magnetospheric plasma waves play a significant role in ring current and radiation belt dynamics, leading to pitch angle scattering loss and/or stochastic acceleration of the particles. During a non‐storm time dropout event on 24 September 2013, intense electromagnetic ion cyclotron (EMIC) waves were detected by Van Allen Probe A (Radiation Belt Storm Probes‐A). We quantitatively analyze a conjunction event when Van Allen Probe A was located approximately along the same magnetic field line as MetOp‐01, which detected simultaneous precipitation of >30 keV protons and energetic electrons over an unexpectedly broad energy range (> 30 keV). Multipoint observations together with quasi‐linear theory provide direct evidence that the observed electron precipitation at higher energy (> 700 keV) is primarily driven by EMIC waves. However, the newly observed feature of the simultaneous electron precipitation extending down to 30 keV is not supported by existing theories and raises an interesting question on whether EMIC waves can scatter such low‐energy electrons. Plain Language Summary: Energetic electrons can move from the magnetosphere into the Earth's upper atmosphere and cause chemical changes in the atmosphere leading to ozone reduction. The present paper studies the physical process that causes such electron precipitation. When a charged particle interacts with a plasma wave, its trajectory can be altered such that the particle falls into the upper atmosphere, but this process occurs only for a specific range of particle energy. In this study, we use one satellite (MetOp‐01) orbiting in the upper atmosphere (altitude 800 km) that can detect particle precipitation, and a Van Allen Probes satellite, which provides wave measurements in the equatorial magnetosphere. During the electron precipitation detected by MetOp‐01, a Van Allen Probes satellite observed strong electromagnetic ion cyclotron (EMIC) waves. Multipoint satellite observations together with quasi‐linear theory provide a direct evidence that the observed electron precipitation is primarily driven by EMIC waves. Another new interesting finding is that the precipitation occurs not only for electrons at high energies (> 1 MeV) but also at low energies (down to 30 keV). This newly observed feature is not supported by existing theories and raises an interesting question whether EMIC waves can interact with such low‐energy electrons as well. Key Points: Strong electromagnetic ion cyclotron (EMIC) waves were observed during a non‐storm time electron dropout event Simultaneous particle precipitation was observed for >30 keV protons and energetic electrons in a broad energy range (> 30 keV) Quasi‐linear theory shows that EMIC waves dominate precipitation of high‐energy electrons but underestimates low‐energy electron precipitation